Assessment of visual function in children with foldable intraocular lens implants - Bakunowicz-Łazarczyk, Alina; Średzińska-Kita, Dorota; Mrugacz, Małgorzata; Szumiński, Michał (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: The aim of the current study was to assess the results of cataract surgery involving implantation of foldable intraocular lenses in children. Material and methods: Cataract surgery with foldable lenses was performed in 60 children. Postoperative visual acuity, endothelial cell density, corneal pachymetry, postoperative astigmatism and complications were analyzed. Results: Quick visual recovery was observed in children after surgery. Only a few postoperative complications occurred. Conclusions: The foldable intraocular lenses are easy to insert. The surgical procedure with foldable lens implantation is a useful and safe method of treatment.